Consideration regarding the deprivation of liberty of juveniles in criminal matters, in light of national and international regulations - CHIHAIA GABRIELA-NICOLETA (Law Review, special issue, Decembre 2019, pp. 173-184, 2019)
This article aims to identify the international legal framework, especially the European one, as well as the national framework regarding the deprivation of liberty of juveniles in criminal procedure proceedings, starting from the correct implementation of the principles that concern the interest of this category of persons and continuing with the situations in which it can be disposed, as well as the impact that such a measure has on the juveniles, but also on the families from which they come from. At the same time, this article presents, on the one hand, the vulnerabilities presented by juveniles in detention, and on the other hand, their main rights, both at European and national level. The importance of monitoring the places in which the juveniles are detained is emphasized, as well as the need for alternatives measures to the deprivation of liberty of juveniles, depending on the different stages of the procedure in which they are involved. This goal is the hardest to achieve in practice, as there are few possibilities for implementing such alternative measures. The criminal justice system for juveniles must be oriented entirely towards respecting the rights and safety of juveniles, to promote their well-being, both physically and mentally, and the deprivation of liberty should be used as a last resort, only in exceptional situations, when it is absolutely necessary to achieve the goals provided by the legislation in this matter.